THE EFFECT OF WORK-LIFE BALANCE AND ORGANIZATIONAL SUPPORT ON EMPLOYEE WELFARE AT TVRI NORTH SUMATRA STATION - Yusnidar; Rahmiatul Aula; Ismed Wijaya; Zulfa Salma Fatin; Tasyaul Askia; Lia Rista (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of Work-Life Balance and Organizational Support on Employee Welfare at TVRI North Sumatra Station. This study was conducted at TVRI North Sumatra Station in January 2025, using a survey method involving 98 employee respondents as samples. Data were collected through a questionnaire in the form of a google form distributed to respondents and then analyzed using multiple linear regression tests and correlation coefficient tests to test the simultaneous and partial influence of the Work-Life Balance and Organizational Support variables on Employee Welfare. The results of the study showed that simultaneously, the Work-Life Balance and Organizational Support variables had a significant effect on Employee Welfare with an F count value of 257.327 which was greater than F table 2.70 and a significance level of 0.000 (<0.05). Partially, Work-Life Balance significantly influences Employee Well-Being, with a calculated t-value of 2.861, which is greater than the t-table of 1.660 and a significance level of 0.005 (<0.05). Organizational Support significantly influences Employee Well-Being, with a calculated t-value of 6.441, greater than the t-table of 1.660 and a significance level of 0.000 (<0.05). The correlation coefficient of 0.919 indicates a very strong relationship between the two variables, while the R2 value of 0.844 indicates that 84.4% of the variation in Employee Well-Being can be explained by Work-Life Balance and Organizational Support, while the remaining 16.6% is influenced by other variables. In conclusion, TVRI North Sumatra Station is recommended to improve its Work-Life Balance policy through work flexibility and equitable distribution of organizational support for all employees. Management also needs to strengthen internal communication and pay attention to workloads to maintain employee well-being.